Portuguese Geography, tropics and late colonialism: proposal and results of a dossier - Oliveira, Francisco Roque de (2022)
Despite some partial studies published in recent years, a comprehensive reading of Portuguese Geography has not yet been carried out in order to understand the role of geographic discourse in “colonial context” and the way in which this same discourse seems to have been reassessed, as the international climate around Portuguese colonial policy from the mid-1950s onwards aggravated (Pimenta et al., 2011; Oliveira and Paiva, 2019; Sarmento, 2019). Postcolonial theory teaches us that colonization not only transformed the colonized world, but also profoundly transformed colonizing societies, thus placing the question of colonialism at the heart of European modernity (Driver, 2006; Butlin, 2009). This means that we departed to this dossier pretending, as a fundamental aim, to gather a set of critical analyses on some of the most representative discourses and practices of Portuguese Geography of the time, on the “tropical world”. In doing so, we propose to contribute to the epistemological renewal of the discipline itself, which, in our view, and in line with Driver (2006), Bruneau (2008), Jazeel (2014), Clayton and Kumar (2019) and Clayton (2020), has not yet sufficiently reflected on this very complex moment in its history.